Comparison among anorexia nervosa adolescents with or without previous overweight, obese, and healthy adolescents - Amianto, Federico; Sertori, Francesca; Davico, Chiara; Marcotulli, Daniele; Vitiello, Benedetto (Frontiers in Psychiatry, 2024)
Background Anorexia nervosa (AN) and obesity (OB) are relevant concerns in adolescence. Despite their contrasting phenotypes, they share common pathogenic origins and may be present in the same individual at different times. We explored the psychopathology and attachment features of adolescents with AN who did (AN-ow) or did not (AN-nw) have previous overweight, compared with OB adolescents and healthy control (HC) adolescents. Method In total, 148 female adolescents referred to an outpatient clinic for an eating disorder (66 for AN and 42 for OB) and 40 HCs were assessed using self-administered instruments that measured parenting, attachment, eating, and general psychopathology. Group differences were tested by analysis of covariance, and correlations between variables were examined. Results AN-ow, AN-nw, and OB adolescents had greater interpersonal distrust and avoidance of relationships, compared with HC adolescents. AN-nw and AN-ow adolescents displayed a higher need for approval and a drive to thinness and interpersonal distrust, compared with HC adolescents. AN-ow adolescents displayed lower paternal care and higher ineffectiveness, asceticism, social insecurity, and depression, compared with HC adolescents. Compared with AN-nw adolescents, AN-ow adolescents felt more ineffective and more ascetic. The dynamics linking the psychopathological features clearly distinguished the four groups. Conclusions AN-ow is a well-identified subtype of AN, with specific features that differ from AN-nw; some of these features are shared with OB. A therapeutic approach tailored to AN-ow adolescents should consider these features.